The Kulbäcksliden Research Infrastructure: a unique setting for northern peatland studies - Noumonvi, Koffi Dodji; Ågren, Anneli M.; Ratcliffe, Joshua L.; Öquist, Mats G.; Ericson, Lars; Tong, Cheuk Hei Marcus; Järveoja, Järvi; Zhu, Wei; Osterwalder, Stefan; Peng, Haijun; Erefur, Charlotta; Bishop, Kevin; et al. (Frontiers in Earth Science, 2023)
Boreal peatlands represent a biogeochemically unique and diverse environment in high-latitude landscape. They represent a long-term globally significant sink for carbon dioxide and a source of methane, hence playing an important role in regulating the global climate. There is an increasing interest in deciphering peatland biogeochemical processes to improve our understanding of how anthropogenic and climate change effects regulate the peatland biogeochemistry and greenhouse gas balances. At present, most studies investigating land-atmosphere exchanges of peatland ecosystems are commonly based on single-tower setups, which require the assumption of homogeneous conditions during upscaling to the landscape. However, the spatial organization of peatland complexes might feature large heterogeneity due to its varying underlying topography and vegetation composition. Little is known about how well single site studies represent the spatial variations of biogeochemical processes across entire peatland complexes. The recently established Kulbäcksliden Research Infrastructure (KRI) includes five peatland study sites located less than 3 km apart, thus providing a unique opportunity to explore the spatial variation in ecosystem-scale processes across a typical boreal peatland complex. All KRI sites are equipped with eddy covariance flux towers combined with installations for detailed monitoring of biotic and abiotic variables, as well as catchment-scale hydrology and hydrochemistry. Here, we review studies that were conducted in the Kulbäcksliden area and provide a description of the site characteristics as well as the instrumentation available at the KRI. We highlight the value of long-term infrastructures with ecosystem-scale and replicated experimental sites to advance our understanding of peatland biogeochemistry, hydrology, ecology, and its feedbacks on the environment and climate system.